NUTRIENTS DECREASE AL TOXICITY TO DROUGHT RESISTANT VARIETY OF GRAM (CICER ARIETINUM VARIETY RSG – 973) - ARCHANAYADAV (International Journal of Pharma and Bio Sciences, 2013)
Aluminum third most abundant element of earth’s crust usually found in bounded form due to its highly reactive nature. Different environmental factors and pollutants decrease yield of food crops.During this study toxicity of aluminum on drought variety of gram (Cicer arietinum variety RSG – 973) was recorded on different parameters. Aluminum decreases its root- shoot length, biomass, dry weight, and R/S ratio at different concentrations; but nutrient supply (Hoagland’s medium) decreases the toxic effects.